Graded Carrier Concentration Absorber Profile for High Efficiency CIGS Solar Cells - Antonino Parisi; Riccardo Pernice; Vincenzo Rocca; Luciano Curcio; Salvatore Stivala; Alfonso C. Cino; Giovanni Cipriani; Vincenzo Di Dio; Giuseppe Ricco Galluzzo; Rosario Miceli; Alessandro C. Busacca (International Journal of Photoenergy)
We demonstrate an innovative CIGS-based solar cells model with a graded doping concentration absorber profile, capable of achieving high efficiency values. In detail, we start with an in-depth discussion concerning the parametrical study of conventional CIGS solar cells structures. We have used the wxAMPS software in order to numerically simulate cell electrical behaviour. By means of simulations, we have studied the variation of relevant physical and chemical parameters—characteristic of such devices—with changing energy gap and doping density of the absorber layer. Our results show that, in uniform CIGS cell, the efficiency, the open circuit voltage, and short circuit current heavily depend on CIGS band gap. Our numerical analysis highlights that the band gap value of 1.40 eV is optimal, but both the presence of Molybdenum back contact and the high carrier recombination near the junction noticeably reduce the crucial electrical parameters. For the above-mentioned reasons, we have demonstrated that the efficiency obtained by conventional CIGS cells is lower if compared to the values reached by our proposed graded carrier concentration profile structures (up to 21%).